Nikah Mut’ah (Kawin Kontrak) Dalam Hukum Perkawinan Islam - Titin Roswitha Nursanthy, Aji; Solikin; Helmi (Collegium Studiosum Journal, 2018)
In essence, marriage is a human inner and outer bond to live together between a man and a woman to form a family (household) that is eternal, happy and prosperous. "A contract that makes it legal for both parties to have fun in accordance with the Shari'a." One of the maqashid syari'ah (basic principles of sharia), which is to protect the offspring. Islam encourages Muslims to marry and celibacy is forbidden. However, there are marriages that are forbidden, which are known as contract marriages (contract marriages). This marriage, which is commonly called a mut'ah marriage, is a marriage that is forbidden by Islam. Uniquely, this mut'ah marriage is even perpetuated and preserved by the Shi'a religion in the name of religion.